The relationship between body image and steroid use in bodybuilding athletes - Hayati, Nur; Haikal, Muhammad Rifki (Science Midwifery, 2024)
Having a strong body is something that most people want, especially men. Efforts to increase muscle are done by exercising at the fitness center or at home, drinking high protein milk and consuming anabolic steroids. Most anabolic steroid users, including bodybuilding athletes, want to have a bigger and more muscular body. This study aims to determine the relationship between body image of bodybuilding athletes and the use of anabolic steroids. This research uses quantitative methods with a cross sectional study design. The sampling technique is purposive sampling. The sample in this study consisted of 70 bodybuilding athletes who consumed anabolic steroids. Self-image measurement uses a self-image questionnaire that is adapted and modified and tested for validity and reliability. The data analysis technique used is the Chi-Square Test. The results of the study showed a p value = 0.017 (p˂0.05), which means there is a significant relationship between the body image of bodybuilding athletes and the use of anabolic steroids.